Enterococcus haemoperoxidus sp. nov. and Enterococcus moraviensis sp. nov., isolated from water - Svec, P; Devriese, L A; Sedlácek, I; Baele, M; Vancanneyt, M; Haesebrouck, F; Swings, J; Doskar, J (International journal of systematic and evolutionary microbiology, 2001)
A polyphasic taxonomic approach was used to study atypical enterococci isolated from surface waters. All strains were characterized by physiological and biochemical tests as well as by genotyping. The results of biochemical tests and tRNA intergenic length polymorphism analysis (tDNA-PCR) divided all studied strains uniformly into two groups. Because these groups were clearly separated from all enterococcal species described to date, 16S rDNA sequence analysis, DNA base composition analysis and DNA-DNA hybridization of representative strains were done to elucidate the taxonomic position of the analysed groups. On the basis of the results obtained, the names Enterococcus haemoperoxidus (type strain CCM 4851T = LMG 19487T) and Enterococcus moraviensis (type strain CCM 4856T = LMG 19486T) are proposed for the two hitherto undescribed species. The type strains and reference cultures have been deposited in the Czech Collection of Microorganisms (CCM), Masaryk University, Brno, Czech Republic, and in the BCCM/LMG Culture Collection, Ghent University, Belgium.
Keywords: terminologie jako téma; Terminology as Topic; DNA bakterií; sekvence nukleotidů; druhová specificita; DNA, Ribosomal; Phylogeny; Enterococcus; Molecular Sequence Data; molekulární sekvence - údaje; zastoupení bazí; Water Microbiology; Phenotype; Genotype; Base Composition; DNA, Bacterial; Base Sequence; fylogeneze; fenotyp; Czech Republic; Species Specificity; ribozomální DNA; Nucleic Acid Hybridization; genotyp; mikrobiologie vody; hybridizace nukleových kyselin; Česká republika